Novel therapeutic approaches in chondrosarcoma. (March 2017) - Polychronidou, Genovefa; Karavasilis, Vasilios; Pollack, Seth M; Huang, Paul H; Lee, Alex; Jones, Robin L
Chondrosarcoma is a malignant tumor of bones, characterized by the production of cartilage matrix. Due to lack of effective treatment for advanced disease, the clinical management of chondrosarcomas is exceptionally challenging. Current research focuses on elucidating the molecular events underlying the pathogenesis of this rare bone malignancy, with the goal of developing new molecularly targeted therapies. Signaling pathways suggested to have a role in chondrosarcoma include Hedgehog, Src, PI3k–Akt–mTOR and angiogenesis. Mutations in IDH1 / 2, present in more than 50% of primary conventional chondrosarcomas, make the development of IDH inhibitors a promising treatment option. The present review discusses the preclinical and early clinical data on novel targeted therapeutic approaches in chondrosarcoma.